Proposing stakeholder communication framework for business positioning among manufacturing-based small and medium enterprise: adopting a public relations approach - Krishnan, Mahadevan; Ahmad, Jamilah (GIAP Journals, 2019)
Purpose: This study proposes the development of a stakeholder communication framework for manufacturing-based Small and Medium Enterprises (SMEs). Methodology: Employing in-depth interviews with fifteen representatives from manufacturing-SMEs who take-up communication roles at the managerial level, this explorative method interprets, extracts relevant themes to facilitate the development of a stakeholder communication framework for this business sector. Main Findings: This study among key representatives of manufacturing SMEs concluded with the following findings. Firstly, these organizations communicate within the closed-loop stakeholder network with less focus to stakeholders beyond the network. Secondly, SMEs reveal a lack of keenness and understanding of the external business environment or the zone beyond the common network. Finally, with reference to the findings, the study suggests a communication framework for manufacturing SMEs through the incorporation of selected public relation models, roles and levels which is regarded as one that conservatively biased owing to the nature of this sector. Implications: The outcome brings a different perspective to the application of PR, particularly in the area of strategic business communication, which expands the research, application, and the future direction of PR. Novelty: This study enables PR to contribute to organizational competitiveness in the context of communication, which is inevitably vital for the positioning and sustenance of this business sector, particularly with the need to expand the communication portfolio towards stakeholders in the present competitive and globalized setting